Generalized Thermoelasticity Problem of a Hollow Sphere Under Thermal Shock (European Journal of Pure and Applied Mathematics, 2009)
This problem deals with the thermo-elastic interaction due to stepinput of temperature on the boundaries of a homogeneous isotropicspherical shell in the context of generalized theories ofthermo-elasticity. Using the Laplace transformation thefundamental equations have been expressed in the form ofvector-matrix differential equation which is then solved by eigenvalue approach. The inverse of the transform solution is carriedout by applying a method of Bellman et al. Stresses, displacementsand temperature distribution have been computed numerically andpresented graphically in a number of figures for copper material.A comparison of the results for different theories (CTE, CCTE,TRDTE(GL), TEWOED(GN-II), TEWED(GN-III)) is presented. When theouter radius of the shell tends to infinity, the correspondingresults agree with that of existing literature.